Sugar Commodity in Gorontalo: Production, Export, Import, Pricing and Distribution System - Supandi Rahman; Rifadli D. Kadir (Gorontalo Development Review, 2021)
This research is directed to find out more about sugar activities in Gorontalo Province by exploring more deeply about Production, Export, Information, Pricing and Distribution Systems at PT. PG Gorontalo Tolangohula Unit. Using qualitative research methods that aim to systematically describe the facts and characteristics of the object or subject being studied appropriately. The results of the study found that the development of sugar production for Large Plantations (PB) and People's Plantations (PR) in Gorontalo tended to fluctuate, sugar exports from Gorontalo abroad did not yet exist, because sugar production was still needed for the needs of Gorontalo Province and its surroundings, namely North Sulawesi and Central Sulawesi Province, to determine the price of sugar refers to the main decision of the Surabaya Board of Directors, of course taking into account several factors, including production which will determine the cost of goods sold from the factory, and in the market, for the system of selling sugar from the factory to the hands of the community is through the auction system.